Examining the Relationship Between Mindfulness, Self-Compassion, and Emotion Regulation in Self-Injury. Issue 3 (3rd July 2022) - Per, Megan; Simundic, Amanda; Argento, Amanda; Khoury, Bassam; Heath, Nancy
Abstract: Objective: The objective of the current study was to investigate whether mindfulness and self-compassion are negatively associated with engagement in non-suicidal self-injury (NSSI) and whether emotion dysregulation would mediate this relation. Method: 343 participants (82.2% female; M age = 23.98; SD = 7.47) were recruited from university and community settings, and completed online questionnaires. Two groups of participants were created: those with lifetime engagement in NSSI ( n = 153) and a comparison group with no prior engagement in NSSI ( n = 190). Results: First, two one-way MANOVAs revealed significant mean differences (NSSI/comparison) across the self-compassion dimensions and specific mindfulness facets. Second, logistic regressions revealed that the self-coldness dimension of self-compassion significantly predicted engagement in NSSI, and specific mindfulness facets (nonjudging and acting with awareness) were found to negatively predict NSSI engagement. Lastly, mediation analyses revealed that emotion dysregulation fully mediated the relationships between both mindfulness total and self-coldness, and NSSI group status. Conclusion: The present study demonstrates preliminary support for the protective role of key mindfulness facets and potential risk of the self-coldness aspect of self-compassion in NSSI engagement. Implications for potential use of treatment protocols may include teaching key aspects of mindfulness and self-compassion as healthier and kinder alternatives to coping with dysregulated emotions. Highlights: Mindfulness and self-compassion significantly differ between NSSI/comparison groups Key mindfulness facets and self-compassion dimensions negatively predict engagement in NSSI Emotion dysregulation fully mediates self-coldness and mindfulness with NSSI group status